Mononuclear phagocytes of the intestine, the skin, and the lung. Issue 1 (November 2014) - Scott, Charlotte L.; Henri, Sandrine; Guilliams, Martin
Summary: Tissues that are in direct contact with the outside world face particular immunological challenges. The intestine, the skin, and the lung possess important mononuclear phagocyte populations to deal with these challenges, but the cellular origin of these phagocytes is strikingly different from one subset to another, with some cells derived from embryonic precursors and some from bone marrow‐derived circulating monocytes. Here, we review the current knowledge regarding the developmental pathways that control the differentiation of mononuclear phagocytes in these barrier tissues. We have also attempted to build a theoretical model that could explain the distinct cellular origin of mononuclear phagocytes in these tissues.